Konstruksi Model Siklus Belajar Kritis-Induktif (SBKI) Berbasis Pendekatan Rasional dan Empirik dalam Pembelajaran PAI - Marwal Blantara Susetyo; Muhamad Parhan; Muhamad Shendyka; Pitra Gosha Patriasya; Yurana Qiyasa (LP2M IAIN Sultan Amai Gorontalo, 2026)
Contemporary Islamic Religious Education (IRE) faces challenges in fostering students' critical reasoning with a strong epistemological foundation. Thus far, critical thinking has often been viewed as a secondary byproduct rather than a systematically designed cognitive process. This qualitative study, employing a literature review method, aims to construct an IRE learning model focused on strengthening critical mindsets through inductive reasoning mechanisms. The research formulates the Critical-Inductive Learning Cycle (CILC) model, which positions inductive inference (istiqra’) at the heart of the students' thinking process. The model is operationalized through four key stages: contextualization (empirical observation), investigation (data exploration), conceptualization (inductive generalization), and actualization (reflection and application). Theoretically, CILC contributes to IRE pedagogy by asserting that reinforcing critical logic aligns with the formation of reflective faith and potentially serves as a cognitive defense mechanism against hoaxes and radicalism. As a conceptual model, CILC requires further empirical testing to validate its effectiveness in classroom practice.